2015
DOI: 10.1210/en.2014-1733
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Ghrelin Acts in the Brain to Control Liver Function and Peripheral Glucose Homeostasis in Male Mice

Abstract: Recent evidence suggests that peripheral ghrelin regulates glucose metabolism. Here, we designed experiments to examine how central acyl ghrelin infusion affects peripheral glucose metabolism under pair-fed or ad libitum feeding conditions. Mice received intracerebroventricular (icv) infusion of artificial cerebrospinal fluid (aCSF), ghrelin, and allowed to eat ad libitum (icv ghrelin ad lib) or ghrelin and pair-fed to the aCSF group (icv ghrelin pf). Minipumps delivered acyl ghrelin at a dose of 0.25 μg/h at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…injection changes in plasma glucose levels were noted (Schwandt et al 2010). Furthermore, the lack of changes in fatty acid levels is in agreement with that reported in mice under a comparable ICV treatment (Stark et al 2015). GHRL treatment did not affect levels of fatty acid, triglyceride or total lipid in the hypothalamus.…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 90%
See 2 more Smart Citations
“…injection changes in plasma glucose levels were noted (Schwandt et al 2010). Furthermore, the lack of changes in fatty acid levels is in agreement with that reported in mice under a comparable ICV treatment (Stark et al 2015). GHRL treatment did not affect levels of fatty acid, triglyceride or total lipid in the hypothalamus.…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 90%
“…The orexigenic effect is in agreement with that observed in most fish species after IP or ICV GHRL treatments (Unniappan et al 2002, Tinoco et al 2014, and is in line to the effect of this peptide in other vertebrates, including mammals (Ló pez et al 2008, Sangiao-Alvarellos et al 2010, Velásquez et al 2011, Martins et al 2013, Stark et al 2015. It is surprising that GHRL did not also increase food intake 6 h after treatment.…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 87%
See 1 more Smart Citation
“…In another report, a low dose of ghrelin administered peripherally produced an increase in FAS and decreases in CPT‐1α mRNAs expression without affecting food intake. Although some reports have shown an increase in liver adiposity with ghrelin treatment (Davies et al ., 2009), others have shown the opposite effect with ghrelin preventing fat accumulation and improving redox state in the liver of high fat‐fed animals (Barazzoni et al ., 2013) but also under caloric restriction (Stark et al ., 2015). Additional factors may account for the differences in results reported by different groups: mouse age and strain, subchronic vs. chronic ghrelin treatment and via of administration (central vs. peripheral).…”
Section: Discussionmentioning
confidence: 99%
“…However, its role on hepatic steatosis is not known. Recent publications have suggested that it may increase liver adiposity through p53 signaling (Davies et al ., 2009; Porteiro et al ., 2013), although others have shown the opposite effect with ghrelin preventing fat accumulation and improving redox state in the liver of high fat‐fed animals (Barazzoni et al ., 2013) and also under pair‐feed conditions (Stark et al ., 2015). The goal of this work was to determine whether deletion of ghrelin might prevent the age‐associated NAFLD and to determine whether its effects are mediated through the p300‐C/EBPα/β pathway.…”
Section: Introductionmentioning
confidence: 99%